Entrepreneurial Marketing and Organizational Entrepreneurship Performance of Small and Medium Enterprises: A Systematic Review - Batoul Shahmohammadi (Journal of Management and Entrepreneurship Research, 2021)
Objective: The purpose of this article was to systematically review the existing articles on entrepreneurial marketing and organizational entrepreneurship of small and medium enterprises. Research Design & Methods: For this purpose, English research related to the keywords entrepreneurial marketing, impact, organizational entrepreneurship and small and medium enterprises were searched in Elsevier, Emerald and Springer databases for the period 2018-2021. In the meantime, 12 related articles were extracted and studied. Findings: The results of this study showed that the dimensions of entrepreneurial marketing improve organizational entrepreneurship indicators in small and medium enterprises. Implications & Recommendations: Entrepreneurial marketing is one of the marketing strategies of small and medium enterprises that helps them grow through entrepreneurship. In fact, entrepreneurial marketing translates important aspects of marketing and entrepreneurship into a comprehensive conceptualization in which marketing becomes the method that firms use to do entrepreneurship. Contribution & Value Added: This article reviewed 12 most recent published articles in terms of entrepreneurial marketing and organizational entrepreneurship to pave the way of finding latest information in this regard.